2012
DOI: 10.1001/archpediatrics.2011.1407
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Television Viewing With Eating Behaviors in the 2009 Health Behaviour in School-aged Children Study

Abstract: Participants: A total of 12 642 students in grades 5 to 10 (mean [SD] age, 13.4[0.09] years; 86.5% participation). Main Exposures: Television viewing (hours per day) and snacking while watching television (days per week).Main Outcome Measures: Eating (Ն1 instance per day) fruit, vegetables, sweets, and sugary soft drinks; eating at a fast food restaurant (Ն1 d/wk); and skipping breakfast (Ն1 d/wk). Conclusion:Television viewing was associated with a cluster of unhealthy eating behaviors in US adolescents after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 63 publications
4
23
0
1
Order By: Relevance
“…For example, in the U.S., a greater availability of energy-dense snack foods and beverages in neighborhood stores has been positively correlated to excess weight among children 6–7 years (49, 52) yet it is unclear how the availability of highly palatable foods within the community relates to a child’s EAH. Further, exposure to food and beverage advertisements via television may mediate the positive associations between increased TV viewing time and child weight status (4850, 5355), yet studies examining the potential association between food and beverage promotions and EAH among children are absent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the U.S., a greater availability of energy-dense snack foods and beverages in neighborhood stores has been positively correlated to excess weight among children 6–7 years (49, 52) yet it is unclear how the availability of highly palatable foods within the community relates to a child’s EAH. Further, exposure to food and beverage advertisements via television may mediate the positive associations between increased TV viewing time and child weight status (4850, 5355), yet studies examining the potential association between food and beverage promotions and EAH among children are absent.…”
Section: Discussionmentioning
confidence: 99%
“…14 Previous evidence suggests that these unique behaviors tend to cluster together within people. 5,6 For example, regular engagement in physical activity in the form of sports or other exercise has been associated with a generally healthier diet, including greater intake of F&V. 7 Conversely, time spent in TV viewing is associated with increased consumption of soda, snacks, and fast food, 8 and decreased consumption of F&V. 9 A more robust understanding of associations among weight-related behaviors may allow for more effective targeting of behavior change in prevention or intervention programs.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, it was observed that watching TV is linked to some unhealthy eating behaviors such as decreased consumption of fruits and vegetables and increased consumption of fast foods in school-age children. [32] It was also observed that exposure to commercials for healthy foods could increase their consumption by preschoolers[7] and by contrast and exposure to commercials for unhealthy foods could increase their consumption among teenagers. [33] Many studies have also shown that more exposure to TV commercials affects food preferences and the demand for the advertised products in preschoolers and schoolchildren.…”
Section: Discussionmentioning
confidence: 99%